Deciphering the Structure Activity Relationship of Nickel Containing Materials towards Electrocatalytic Oxidation of Urea. Issue 9 (1st September 2022) - Li, Liang; Li, Liuqiang; Huang, Yuanxing; Zhao, Junkai; Jin, Yunjing; Yu, Liu
Abstract : Nickel based materials have been extensively reported to be highly effective for the electrochemical oxidation of urea in the wastewater, which are critical for the energy utilization as well as contamination elimination. In this study, two Ni containing materials of nickel-aluminum layered double hydroxides (NiAl-LDH) and metal organic framework (Ni-MOF) were synthesized and compared with Ni disk towards urea oxidation reaction (UOR). Physical characterization proved the existence of Ni with the same valence of +2 in the as-prepared catalysts. Moreover, the electrochemical analysis showed that more active Ni centers with surface concentrations of 1.01 × 10 −6 and 1.17 × 10 −6 mol cm −2 existed in both NiAl-LDH and Ni-MOF, which was significant higher than Ni disk of 3.74 × 10 −7 mol cm −2 . Moreover, Ni-MOF was found to be a better catalyst due to its lower activated energy, tafel slope & overpotential as well as higher stable current density and turnover frequency (TOF) value than NiAl-LDH. This phenomenon might be explained by the protection of Ni 2+ by the lattice of layered double hydroxides, which led to an obstacle for its transformation to Ni 3+ and thus obviously hindered UOR.